Assessment of Parameter Sensitivity in Rainfall-Runoff Modelling for Peninsular Malaysia - Mohamad Arbai Nurul Afiqah; Masayasu Irie; Chong Khai Lin (E3S Web of Conferences)
The parameter sensitivity is identified in the usage of the Rainfall-Runoff-Inundation model, also known as RRI for Peninsular Malaysia. The data used in the analysis were obtained from 518 rainfall and 5 evaporation stations from 2017 to 2020 with topography resolution of 1 km. Subjected to overland flow behaviour condition, six model parameters were individually tested to observe the significance of the changes in the runoff outputs from the model default values. The comparisons were conducted in terms of average, maximum, and minimum discharge throughout the period. The results showed land roughness is the most sensitive parameter, followed by parameters of river width, river depth, and river roughness. The study helps researchers in calibrating RRI model for the application in Peninsular Malaysia.